Pengaruh Bukti Langsung, Kehandalan, Jaminan, Daya Tanggap dan Empati, Terhadap Kepuasan Pasien pada Puskesmas - Sondakh, Billy Rolly; Tampi, Johnny R. E.; Tumbel, Tinneke M. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The goal of the study is to test the effects of efidence directly, reliability, asurance, response, empathy for the patient’s satisfation at the medical center . The samples used in this study number one hundred. As for a sample method of taking by purposive sampling. The data analysis method used is quantitative analysis by using the validity test and reliability test, test f, determinative coefficient, test t and regression analysis. Using multiple regression methods, you might conclude that the evidence variable immediately has a positive and significant impact on consumer satisfaction. Whereas reliability has a positive but insignificant effect on consumer satisfaction. Guarantee has a positive but insignificant effect on consumer satisfaction. The response has a positive but insignificant effect on consumer satisfaction. For empathy, it has no positive or insignificant impact on consumer satisfaction. Simultaneous evidence of direct,reliability can signifikantly affect costumers satisfaction with f counts greater than the significance number. The resulting coefficient determination is 0.322 which means 32.2 percent of variable changes in consumer satisfaction are explained by common evidence, reliability, guarantees, response and empathy changes, while 67.8 percent is explained by other non-research variables.